2018
DOI: 10.1097/cmr.0000000000000478
|View full text |Cite
|
Sign up to set email alerts
|

Real-world performance and utility of a noninvasive gene expression assay to evaluate melanoma risk in pigmented lesions

Abstract: About 3 million surgical pigmented skin lesion biopsies are performed each year in the USA alone to diagnose fewer than 200 000 new cases of invasive melanoma and melanoma in situ using the current standard of care that includes visual assessment and histopathology. A recently described noninvasive adhesive patch-based gene expression rule-out test [pigmented lesion assay (PLA)] may be helpful in identifying high-risk pigmented skin lesions to aid with surgical biopsy decisions. The main objective of this util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 9 publications
1
96
0
1
Order By: Relevance
“…The recently described pigmented lesion assay (PLA), is a molecular tool for clinicians that uses gene expression profiling to aid in making biopsy decisions to rule out melanoma (Childs, 2018;Ferris et al, 2017Ferris et al, , 2018Gerami et al, 2017;Hornberger and Siegel, 2018;Rivers et al, 2018;Yao et al, 2016Yao et al, , 2017. Using adhesive patches for noninvasive sample collection, the PLA analyzes the expression of two genes, LINC and PRAME, both of which are often increased in melanoma (Gerami et al, 2017;Yao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently described pigmented lesion assay (PLA), is a molecular tool for clinicians that uses gene expression profiling to aid in making biopsy decisions to rule out melanoma (Childs, 2018;Ferris et al, 2017Ferris et al, , 2018Gerami et al, 2017;Hornberger and Siegel, 2018;Rivers et al, 2018;Yao et al, 2016Yao et al, , 2017. Using adhesive patches for noninvasive sample collection, the PLA analyzes the expression of two genes, LINC and PRAME, both of which are often increased in melanoma (Gerami et al, 2017;Yao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The performance metrics of the PLA were validated against histopathologic consensus reads (by three dermatopathologists specializing in pigmented lesions) (Gerami et al, 2017). Compared with the current standard of visual assessment followed by histopathology, the PLA has a lower false negative rate (9% vs. 16%), a higher negative predictive value (99% vs. 83%), and a higher specificity (<32% vs. >69%) (Ferris et al, 2017(Ferris et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…This challenge has resulted in the standard practice of ensuring complete removal of lesions characterized as SDN. [2][3][4] While some melanomas do arise within dysplastic nevi, the majority do not, and some propose that routine re-excision of all SDN may not be necessary. 5,6 Improved ability to stratify the malignant potential in these borderline lesions could spare patients unnecessary procedures.…”
mentioning
confidence: 99%
“…7,9 Additionally, high-risk DNA driver mutations (BRAF non-V600E, NRAS, TERT) commonly found in early-stage melanoma can also be assessed using the same adhesive patchbased skin sample collection platform. 2,10 Combining these DNA and RNA risk factors enhances the ability to non-invasively detect melanoma. 10 The objective of our current study was to evaluate the expression of LINC, PRAME, and select melanoma driver mutations in clinically-challenging borderline lesions such as SDN and compare findings to lesions at both ends of the pigmented lesion spectrum where less controversy about management exists.…”
mentioning
confidence: 99%
“…In our patient, there was 100% concordance for 6 lesions with moderate-/high-risk test results and melanoma diagnoses. Although prior studies reported a specificity of 70% for the PLA test, 2 , 3 a more recent real-world study by Ferris et al 4 yielded a positive predictive value of only 37%. Second, we avoided biopsy of 14 clinically suspicious lesions with low-risk results, which illustrates the utility of the test for increasing confidence that particular melanocytic lesions are benign.…”
Section: Discussionmentioning
confidence: 89%